Implementasi Standar Operasional Prosedur Dalam Meningkatkan Mutu Layanan Administrasi Pendidikan Di Madrasah Ibtidaiyah Negeri 6 Sinar Rejeki Jati Agung Lampung Selatan - Khusna Nazila; Etika Pujianti; Nur Widiastuti (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
The main objective of this study is to analyze the implementation of Standard Operating Procedures (SOPs) in improving the quality of educational administration services at State Islamic Elementary School 6 Sinar Rejeki Jati Agung, South Lampung. This study uses a descriptive qualitative approach to explore the implementation of Standard Operating Procedures (SOPs) in improving the quality of educational administration services at State Islamic Elementary School 6 Sinar Rejeki Jati Agung, South Lampung. The units of analysis included the principal, teachers, administrative staff, and parents. Data were collected through semi-structured interviews, participant observation, and documentation, then analyzed thematically to identify patterns, themes, and relationships between SOPs and service quality. Validity was maintained through triangulation and member checking, allowing this study to illustrate the technical effectiveness of SOPs as well as their social implications and public trust. The results of this study indicate that the implementation of Standard Operating Procedures (SOPs) at State Islamic Elementary School 6 Sinar Rejeki Jati Agung has been proven to improve the quality of educational administration services. SOPs expedite the registration process, manage attendance, and report grades, while reducing duplication and uncertainty. In addition, SOPs strengthen transparency and accountability through clear documentation, increasing parental and community trust. Their implementation also improves interaction and collaboration between teachers and staff. Overall, SOPs serve as strategic guidelines that support efficiency, professionalism, and a disciplined and collaborative work culture.